Surgical recurrent paralysis - Castillo, Luis A.; Blasiak, José; Gallego, Antonio; Suárez, Hamlet E. (Cirugía del Uruguay, 1975)
The authors base their experience. on 57 patients with laryngeal paralysis, studied during a three-year period. They review the functional anatomy of the larynx insisting upan its innervation and circulation. Its very rich vascular net is closely related to the circulation of the thyroid gland. The authors experimental studies prove the particular characteristics of the laryngeal muscles and their early damage on anoxia. They insist upon the spirometric tests, an objetive indirect method used to measure glotic sufficiency. The medical treatment and the different surgical techniques used are discussed. 11 patients were operated upan: 9 of them with bilateral paralysis, in which the best results were obtained with the lateral approach and 2 with unilateral paralysis, both of them treated by cartilage graft through anterior route, with satisfactory results.